(untitled) (Research, Society and Development, 2021)
In this work, we carry out a reflection around issues regarding work in the Brazilian fashion and clothing industry – one of the oldest activities performed by mankind. The objective of conceiving such work was to be able to understand the main aspects related to precariousness and inhuman work in this field. As far as the methodology applied to the study goes, this research is characterized as qualitative, and of descriptive and bibliographic type. As a result, in general, it can be observed that the precarious and flexible working relationships are utilized by companies as a means of profitability. However, when using this mechanism, worker’s rights, which are the most fragile part of this process, are the most affected, and in many cases, workers find themselves in situations similar to slavery, working in a forced way, with exhaustive workdays, and in degrading conditions.